Evaluation of Weld Joint Quality in Drill Pipe Based on Heat Input Variation in Bending and Microstructure Test - Alexander Sebayang; Efrata Tarigan; Idham Kamil; Joko Sutrisno (Malikussaleh University, Aceh, Indonesia, 2026)
Drill pipes are critical components in oil, gas, and geothermal drilling operations, serving as conduits for circulating drilling fluids from the surface to the borehole while simultaneously transmitting mechanical loads. Due to severe operating conditions, including high pressure, cyclic loading, and corrosive environments, the integrity of welded joints in drill pipes must be ensured through appropriate welding methods and quality evaluation. This study investigates the effects of heat input variations on the mechanical properties and microstructural characteristics of welded joints in ASTM A106 Grade B steel pipes produced using Shielded Metal Arc Welding (SMAW) and Gas Metal Arc Welding (GMAW). Welding was performed using a single V-groove butt joint configuration in the 1G position with a constant welding current of 140 A. SMAW welding employed E7018 electrodes, while GMAW utilized ER70S-6 filler wire with a shielding gas mixture of 70% argon and 30% CO?. Mechanical performance was evaluated through bending tests, including root and face bends, in accordance with applicable standards. In addition, microstructural analysis of the weld metal and Heat Affected Zone (HAZ) was conducted using optical microscopy after chemical etching to identify phase distribution and grain morphology. The bending test results revealed that SMAW-welded joints exhibited higher ultimate stress (?u) values than GMAW-welded joints. The highest ?u value of 1327.14 MPa was obtained from the SMAW face bend specimen, while the lowest value of 922.10 MPa was recorded for the GMAW root bend specimen. Furthermore, face-bend tests consistently yielded higher ?u values than root-bend tests for both welding methods, indicating superior mechanical resistance at the weld surface. Microstructural observations showed that SMAW welds exhibited coarser ferrite–pearlite grain structures due to higher heat input and slower cooling rates associated with flux-covered electrodes. In contrast, GMAW welds exhibited finer, more homogeneous microstructures due to lower heat input and faster cooling rates. These differences in microstructure significantly influenced the mechanical behaviour of the welded joints. The findings of this study provide valuable insights into selecting welding methods for ASTM A106 Grade B pipes, particularly in applications that require a balance between mechanical strength and microstructural stability